Single cell RNA-seq reveals cellular and transcriptional heterogeneity in the splenic CD11b+Ly6Chigh monocyte population expanded in sepsis-surviving mice - Haruki Watanabe; Minakshi Rana; Myoungsun Son; Pui Yan Chiu; Yurong Fei-Bloom; Kwangmin Choi; Betty Diamond; Barbara Sherry (Molecular Medicine)
Abstract Background Sepsis survivors exhibit immune dysregulation that contributes to poor long-term outcomes. Phenotypic and functional alterations within the myeloid compartment are believed to be a contributing factor. Here we dissect the cellular and transcriptional heterogeneity of splenic CD11b+Ly6Chigh myeloid cells that are expanded in mice that survive the cecal ligation and puncture (CLP) murine model of polymicrobial sepsis to better understand the basis of immune dysregulation in sepsis survivors. Methods Sham or CLP surgeries were performed on C57BL/6J and BALB/c mice. Four weeks later splenic CD11b+Ly6Chigh cells from both groups were isolated for phenotypic (flow cytometry) and functional (phagocytosis and glycolysis) characterization and RNA was obtained for single-cell RNA-seq (scRNA-seq) and subsequent analysis. Results CD11b+Ly6Chigh cells from sham and CLP surviving mice exhibit phenotypic and functional differences that relate to immune function, some of which are observed in both C57BL/6J and BALB/c strains and others that are not. To dissect disease-specific and strain-specific distinctions within the myeloid compartment, scRNA-seq analysis was performed on CD11b+Ly6Chigh cells from C57BL/6J and BALB/c sham and CLP mice. Uniform Manifold Approximation and Projection from both strains identified 13 distinct clusters of sorted CD11b+Ly6Chigh cells demonstrating significant transcriptional heterogeneity and expressing gene signatures corresponding to classical-monocytes, non-classical monocytes, M1- or M2-like macrophages, dendritic-like cells, monocyte-derived dendritic-like cells, and proliferating monocytic myeloid-derived suppressor cells (M-MDSCs). Frequency plots showed that the percentages of proliferating M-MDSCs (clusters 8, 11 and 12) were increased in CLP mice compared to sham mice in both strains. Pathway and UCell score analysis in CLP mice revealed that cell cycle and glycolytic pathways were upregulated in proliferating M-MDSCs in both strains. Notably, granule protease genes were upregulated in M-MDSCs from CLP mice. ScRNA-seq analyses also showed that phagocytic pathways were upregulated in multiple clusters including the classical monocyte cluster, confirming the increased phagocytic capacity in CD11b+Ly6Chigh cells from CLP mice observed in ex vivo functional assays in C57BL/6J mice. Conclusion The splenic CD11b+Ly6Chigh myeloid populations expanded in survivors of CLP sepsis correspond to proliferating cells that have an increased metabolic demand and gene signatures consistent with M-MDSCs, a population known to have immunosuppressive capacity.